A STUDY OF ETHICAL ENTREPRENEURSHIP COMPETENCY USING EXPERIENTIAL LEARNING FOR MATHAYOMSUKSA 2 STUDENTS AT ROONG-AROON SCHOOL - Thanakoolkaweepong, Teerasak (Journal of Education and Innovation, 2025)
The purposes of this research were to 1) study the ethical entrepreneurship competency using experiential learning, 2) Study students’ learning achievement in the course Financial Literacy Studio: Value Creator using experiential learning compared to the 70% threshold, and 3) Study the relationship between ethical entrepreneurship competency and academic achievement in the Financial Literacy Studio: Value Creator course of grade 8 students. The population consisted of 22 students in Mathayomsuksa 2/2 of Roong-Aroon School by cluster random sampling. The research instruments were 6 lesson plans, each containing details of experiential learning activities, specific competency assessment tools, and different types of academic achievement assessments. The results showed that 1) There were 20 students out of 22 students, accounting for 90.91 percent of the total students, who exhibited the ethical entrepreneurship competency at a level of "Mastering" or higher after experiential learning, 2) There were 19 students, or 86.36 percent, achieved the learning achievement in the Financial Literacy Studio: Value Creator course higher than 70 percent of the full score at .01 level of significance, and 3) There is a very high positive correlation between the ethical entrepreneurship competency and academic achievement in the Financial Literacy Studio: Value Creator course, with a correlation coefficient of 0.825, at .01 level of significance.